Artemether-lumefantrine versus dihydroartemisinin-piperaquine for treatment of malaria: a randomized trial - Kamya, MR; Yeka, A; Bukirwa, H; Lugemwa, M; Rwakimari, J; Staedke, S; Talisuna, A; Greenhouse, B; Nosten, F; Rosenthal, P; Wabwire-Mangen, F; Dorsey, G (Public Library of Science, 2007)
OBJECTIVES: To compare the efficacy and safety of artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DP) for treating uncomplicated falciparum malaria in Uganda. DESIGN: Randomized single-blinded clinical trial. SETTING: Apac, Uganda, an area of very high malaria transmission intensity. PARTICIPANTS: Children aged 6 mo to 10 y with uncomplicated falciparum malaria. INTERVENTION: Treatment of malaria with AL or DP, each following standard 3-d dosing regimens. OUTCOME MEASURES: Risks of recurrent parasitemia at 28 and 42 d, unadjusted and adjusted by genotyping to distinguish recrudescences and new infections. RESULTS: Of 421 enrolled participants, 417 (99%) completed follow-up. The unadjusted risk of recurrent falciparum parasitemia was significantly lower for participants treated with DP than for those treated with AL after 28 d (11% versus 29%; risk difference [RD] 18%, 95% confidence interval [CI] 11%-26%) and 42 d (43% versus 53%; RD 9.6%, 95% CI 0%-19%) of follow-up. Similarly, the risk of recurrent parasitemia due to possible recrudescence (adjusted by genotyping) was significantly lower for participants treated with DP than for those treated with AL after 28 d (1.9% versus 8.9%; RD 7.0%, 95% CI 2.5%-12%) and 42 d (6.9% versus 16%; RD 9.5%, 95% CI 2.8%-16%). Patients treated with DP had a lower risk of recurrent parasitemia due to non-falciparum species, development of gametocytemia, and higher mean increase in hemoglobin compared to patients treated with AL. Both drugs were well tolerated; serious adverse events were uncommon and unrelated to study drugs. CONCLUSION: DP was superior to AL for reducing the risk of recurrent parasitemia and gametocytemia, and provided improved hemoglobin recovery. DP thus appears to be a good alternative to AL as first-line treatment of uncomplicated malaria in Uganda. To maximize the benefit of artemisinin-based combination therapy in Africa, treatment should be integrated with aggressive strategies to reduce malaria transmission intensity.